Retraction Note: CT, MRI, and 18F-FDG PET/CT imaging features of seven cases of adult pancreatoblastoma - Mengnan Wu; Jiongbin Lin; Zhuangsheng Liu; Zhiming Huang; Ruoning Wang (BMC Medical Imaging, 2024)
This article has been retracted. Please see the Retraction Notice for more detail: https://doi.org/10.1186/s12880-022-00958-4